Estudio de prefactibilidad para la instalación de una planta de producción de barras empanizadas precocidas de pescado amazónico (Piaractus brachypomus) - Angeles Nuñez, Erick Javier (2023)
The objective of this pre-feasibility study is to determine the market, technical, environmental, economic-financial, and social viability for the installation of a precooked breaded bars of paco production plant. In “Chapter I. General aspects” the problem, the objectives, the justification of the topic and the hypothesis were determined. In “Chapter II. Market study” presents the description of the product, the analysis of the industrial sector, the business model, the analysis of the supply and demand of the project, which reflects an amount of 564 740 boxes for the fifth year of the project. In “Chapter III. Plant location” the most optimal location for the plant was determined based on a macro and micro location analysis using the factor ranking methodology, in which the district of Villa El Salvador in Lima was chosen. In “Chapter IV. Plant size” the plant size was calculated considering the market, productive resources, technology and the break-even point, so the calculated plant size was 564 740 boxes. In “Chapter V. Project engineering” the technical description of the product, the regulatory framework, the production process, the installed capacity, which is 836 815 boxes per year determined by the packaging process, the quality of the product, environmental impact, occupational health and safety, maintenance, supply chain, production program and the plant distribution, in which the production area was calculated according to Guerchet of 129,6 m2 and a total area of 1221 m2 were described. In “Chapter VII. Budgets and project evaluation” a total investment of S/ 1 759 273, a Financial NPV of S/ 1 057 583, that being a positive amount means that the project is profitable, a Financial IRR of 56% higher than the COK of 18,36%, which means that it exceeds the expectations of the stakeholders and a recovery period of 2 years 6 months and 24 days was determined Finally, the “Chapter VIII. Social evaluation” evaluates the impact of the project in the society and the benefits it generates for the nearby population. Therefore, an added value of S/ 7 579 547 was calculated.